SOAP - Zhang, Grace (Ars Medica, 2020)
The SOAP (Subjective, Objective, Assessment, and Plan) format is taught very early in medical education as a way of structuring a note in the medical chart; it thus has a very formative effect on subsequent learning and forms basic categories into which all medical information is placed. This poem satirizes physicians' reverence of the SOAP note as a foundation of written communication, highlights some of its shortcomings, and also explores how deeply formatting choices can shape the way physicians view their patients.